Penguatan Kompetensi Guru Melalui Media Pembelajaran Comic Strip Dalam Internalisasi Nilai Moderasi Beragama - Wahyu Fitrina Defi; Reni Septrisia (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2024)
The programs regarding religious moderation are activities that are in line with the principles of the state. The essence of this program is that everything carried out in an agency must be moderate and not extreme left or right. This means that attitudes of tolerance, mutual respect, non-violence, and upholding the foundations of the state are manifestations of religious moderation. This service is motivated by the culture in Pariaman which does not accept the presence of immigrants, especially ethnic Chinese, because of the history of the previous Khanso incident. The aim of this service is to socialize religious moderation through strengthening teacher competence using comic strips as a learning medium for teachers that will be used in the learning process. The service partners are 15 teachers of MTSN 1 and MTSN 2 Pariaman. The method used in this service is PAR. It was held on 9-10 December 2023 at the Joyo Makmur Pariaman. The result are teachers will be able to create comics based on religious moderation according to the subjects they teach and make students understand the concept of religious moderation. Hopefully the message in the comic will be conveyed and students can apply it in their daily lives.